2009
DOI: 10.1016/j.mad.2008.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution of telomerase activity and body mass in mammals: From mice to beavers

Abstract: Telomerase is repressed in the majority of human somatic tissues. As a result human somatic cells undergo replicative senescence, which plays an important role in suppressing tumorigenesis, and at the same time contributes to the process of aging. Repression of somatic telomerase activity is not a universal phenomenon among mammals. Mice, for example, express telomerase in somatic tissues, and mouse cells are immortal when cultured at physiological oxygen concentration. What is the status of telomerase in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 86 publications
(118 reference statements)
4
94
0
Order By: Relevance
“…In contrast, in the smaller and much shorter-lived mice telomerase is expressed in several somatic tissues, for instance the liver, and the telomeres are not shortened with cell division. These striking differences among the two determinately growing mammals were explained by disparities in life history and body mass (Gorbunova and Seluanov 2009). Animals with indeterminate growth are thought to express telomerase in their tissues also in the adult stages as was shown for the rainbow trout Oncorhynchus mykiss and the American lobster Homarus americanus (Klapper et al 1998).…”
Section: Reproductive and Mechanical Senescencementioning
confidence: 89%
See 1 more Smart Citation
“…In contrast, in the smaller and much shorter-lived mice telomerase is expressed in several somatic tissues, for instance the liver, and the telomeres are not shortened with cell division. These striking differences among the two determinately growing mammals were explained by disparities in life history and body mass (Gorbunova and Seluanov 2009). Animals with indeterminate growth are thought to express telomerase in their tissues also in the adult stages as was shown for the rainbow trout Oncorhynchus mykiss and the American lobster Homarus americanus (Klapper et al 1998).…”
Section: Reproductive and Mechanical Senescencementioning
confidence: 89%
“…For instance, mice express telomerase in some somatic tissues and mole rats show negligible senescence despite determinate growth (Buffenstein 2008;Gorbunova and Seluanov 2009). And the water flea Daphnia magna shows reproductive and tissular senescence in its final period of life despite indeterminate growth (Schulze-Röbbecke 1951).…”
Section: Suitability Of the Marbled Crayfish For Research On Genetic mentioning
confidence: 99%
“…Early studies suggested that even among mammals there are significant differences in telomerase levels in adult tissues (Gomes et al, 2010;Greenberg et al, 1998;Prowse & Greider, 1995). In rodents telomerase activity inversely correlates with body mass (Gorbunova & Seluanov, 2009). Recently, an exhaustive analysis of telomerase activity and telomere length in mammals has been reported (Gomes et al, 2011).…”
Section: Telomerase Regulation In Different Speciesmentioning
confidence: 99%
“…However, the target sizes of murine SC pools for mutations in most tissues are likely manifoldly smaller than their human counterparts due to body size. Various mechanisms have been proposed to suppress cancer incidence in larger mammals (22)(23)(24), such as the possible evolution of multiple copies of tumor suppressor genes or suppression of telomerase activity with the evolution of larger body size. These mechanisms could help explain Peto's paradox, whereby larger mammals having much larger SC pool sizes do not develop proportionally more cancers.…”
mentioning
confidence: 99%